COLOURS IN PAINTING (CHITRKALA ME RANG) - Dhiman, Kiran (International Journal of Research -GRANTHAALAYAH, 2014)
Colours are life of paintings. Without colours ‘painting’ seems incomplete and dull. Painting is visual expression, which is made combining two basic elements ‘drawing’ and ‘colouring’. Colours add the charm to an artwork. Monochrome shade is also having its own value but colours make it more appealing and lively. Since the upper paleolithic prehistoric times human being practice ’art’ specially paintings in rock shelting to express their thoughts, which means it was a mode of communication from the beginning. This art creates, for the viewer, a degree of experiential contact with prehistoric art. It provides the basis for entering into the changing aspects of the living arts of man.